A Mechanistic Clinical Trial Using (R)- Versus (S)-Propafenone to Test RyR2 (Ryanodine Receptor) Inhibition for the Prevention of Atrial Fibrillation Induction. (27th September 2022) - Shoemaker, M. Benjamin; Yoneda, Zachary T.; Crawford, Diane M.; Akers, Wendell S.; Richardson, Travis; Montgomery, Jay A.; Phillips, Sharon; Shyr, Yu; Saavedra, Pablo; Estrada, Juan C.; Kanagasundram, Arvindh; Shen, Sharon T.; et al.
Abstract : Background: Experimental data suggest ryanodine receptor-mediated intracellular calcium leak is a mechanism for atrial fibrillation (AF), but evidence in humans is still needed. Propafenone is composed of two enantiomers that are equally potent sodium-channel blockers; however, (R )-propafenone is an ryanodine receptor inhibitor whereas (S )-propafenone is not. This study tested the hypothesis that ryanodine receptor inhibition with (R )-propafenone prevents induction of AF compared to (S )-propafenone or placebo in patients referred for AF ablation. Methods: Participants were randomized 4:4:1 to a one-time intravenous dose of (R )-propafenone, (S )-propafenone, or placebo. The study drug was given at the start of the procedure and an AF induction protocol using rapid atrial pacing was performed before ablation. The primary endpoint was 30 s of AF or atrial flutter. Results: A total of 193 participants were enrolled and 165 (85%) completed the study protocol (median age: 63 years, 58% male, 95% paroxysmal AF). Sustained AF and/or atrial flutter was induced in 60 participants (84.5%) receiving (R )-propafenone, 60 (80.0%) receiving (S )-propafenone group, and 12 (63.2%) receiving placebo. Atrial flutter occurred significantly more often in the (R )-propafenone (N=23, 32.4%) and (S )-propafenone (N=26, 34.7%) groups compared to placebo (N=1, 5.3%, P =0.029). There was no significant difference between (R )-propafenone and (S )-propafenone for the primary outcome of AF and/or atrial flutter induction in univariable ( P =0.522) or multivariable analysis ( P =0.199, adjusted for age and serum drug level). Conclusions: There is no difference in AF inducibility between (R )-propafenone and (S )-propafenone at clinically relevant concentrations. These results are confounded by a high rate of inducible atrial flutter due to sodium-channel blockade. Registration: https://clinicaltrials.gov ; Unique Identifier: NCT02710669.